Kualitas Pelayanan Publik dalam Pengurusan Kartu Identitas Anak di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bintan - Halawa, Sri Okta Riani; Rumzi Samin; Firman Firman (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
To find out the quality of public services in the administration of Child Identity Cards (KIA) at the Bintan Regency Population and Civil Registration Office, researchers used a qualitative approach with data collection techniques, namely interviews, observation, and documentation. Data analysis techniques used were data reduction, data presentation, and conclusion. In this research, researchers used the theory of Pararusman ddk (In Tjiptnono, 1996: 70) to determine the quality of public services in the management of children's identity cards at the Population and Civil Registration Office of Bintan Regency as follows: Reliability, Tangibles, Assurance (Assurance), Empathy (Empaty), and Responsiveness (Responsiveness) have quality where service officers are fast and timely in service. It's just that there are still obstacles and obstacles to proper guarantees, there are still obstacles which are inadequate facilities and sometimes the network is unstable in issuing documents for managing Child Identity Cards. has not run optimally in the management of Child Identity Cards (KIA).